2018
DOI: 10.1136/bcr-2018-226870
|View full text |Cite
|
Sign up to set email alerts
|

Acute cholecystitis and gallbladder perforation leading to massive haemoperitoneum in a patient taking rivaroxaban

Abstract: We present the case of an 80-year old man taking rivaroxaban for atrial fibrillation who sustained massive intra-abdominal bleeding in the setting of acute cholecystitis. CT scan on admission revealed evidence of active bleeding into the gallbladder lumen and gallbladder perforation. Immediate resuscitation was commenced with intravenous fluids, antibiotics and blood products. Despite attempts to correct coagulopathy, the patient’s haemodynamic status deteriorated and an emergency laparotomy was performed, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…Few studies have previously reported on free rupture of the gallbladder with massive intraabdominal bleeding. 4,7,8 The reported cases focus primarily on increased risk of bleeding in patients with patients on anticoagulants or those who have bleeding diathesis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Few studies have previously reported on free rupture of the gallbladder with massive intraabdominal bleeding. 4,7,8 The reported cases focus primarily on increased risk of bleeding in patients with patients on anticoagulants or those who have bleeding diathesis.…”
Section: Discussionmentioning
confidence: 99%
“…This is similar for other cases where patients were taking anticoagulants and presented with hemorrhagic cholecystitis. 4,[9][10][11] The patient later presented with substernal and subxiphoid pain that was worked up extensively given his cardiac history. This was likely related to early onset of acute on chronic cholecystitis, which was delayed in diagnosing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All three patients were transitioning from warfarin to rivaroxaban when they experienced a spontaneous vitreous hemorrhage [36]. Hemoperitoneum from atraumatic splenic rupture and in the setting of acute cholecystitis in patients taking DOACs has been reported [37,38].…”
Section: Epidemiologymentioning
confidence: 99%
“…Bleeding complications from direct oral anticoagulant use[10,20,[22][23][24][25][26][27][30][31][32][33][34][35][37][38][39]42].…”
mentioning
confidence: 99%